Studi Elektrokimia Sistem Fe(III)/Fe(II) dalam Lelehan KOH secara Voltametri Siklis - Buchari Buchari; Suprapto Suprapto (Institut Teknologi Bandung, 2004)
Electrochemical study of Fe(III)/Fe(II) system in molten KOH by cyclic voltammetry has been investigated using platinum wire, antimony wire and gold wire as working, reference and counter electrodes respectively. The solution of ferric and ferrous salts in molten KOH were maintened at 210 oC. Cyclic voltammogram of FeCl3 and FeCl2 showed electrochemical system of Fe3+/Fe2+ and Fe3+/Fe at the electrode potentials : 1.3 and 0.8 V respectively versus antimony electrode. In molten KOH, Fe(CN)63- decomposed to Fe3+, meanwhile Fe(CN)64- is oxidised to Fe(CN)63- and followed by its decomposition to Fe3+. The electrochemical parameters in aqueous to be tested in this study are applicable in molten KOH.